High-accuracy and high-efficiency fringe projection profilometry - Huang, NengQi (Nanyang Technological University, 2023)
Fringe Projection Profilometry (FPP) system consists of four main measurement stages: calibration, phase measurement, correspondence, and reconstruction, each designed to solve some specific problems in the system. In this report, a comprehensive guide of how-to setup and use the FPP system is descripted, including new software developed for enhanced performance. One method was suggested to improve the accuracy during the calibration stage, by integrating the subpixel edge detection. This method was shown to be able to achieve higher accuracy than the traditional method in detecting the center of the circle. A phase unwrapping method was proposed to improve the efficiency in phase measurement stage, by generating an additional staggered wrapped phase from the original wrapped phase and divide the period of fringe order into two parts. The proposed method demonstrated improved performance and robustness compared to the Tri-PU Method.